Social Capital as a Success Factor for Collective Farmers Marketing Initiatives - Megyesi, Boldizsár; Kelemen, Eszter; Schermer, Markus (The International Journal of Sociology of Agriculture and Food, 2011)
This study aims at uncovering how social capital at micro and macro levels contributes to the success of farmers’ co-operation and how imbalances between the different forms of social capital can hamper collective action among farmers. Using a case-study approach, we analyse two collective farmers marketing initiatives from Austria and Hungary, which have emerged in very diverse political and social environments and followed different development paths. Differences in the performance of these organizations can be partly traced back to variations in the contextual environment. However, the empirical data suggest that social capital plays an important role as well, since it is crucial for mobilizing the initial set of different forms of other capitals like natural, physical, financial and human capitals. The aim of this article is to understand the dynamics and impacts of different configurations of social capital and its contribution to the economic success of collective initiatives. Based on the empirical findings collective farmers marketing initiatives can deduct ways to consciously appraise and invest in social capital.